Physical Disruption of Solid Tumors by Immunostimulatory Microrobots Enhances Antitumor Immunity. Issue 49 (11th October 2021) - Zhou, Jiarong; Karshalev, Emil; Mundaca‐Uribe, Rodolfo; Esteban‐Fernández de Ávila, Berta; Krishnan, Nishta; Xiao, Crystal; Ventura, Christian J.; Gong, Hua; Zhang, Qiangzhe; Gao, Weiwei; Fang, Ronnie H.; Wang, Joseph; et al.
Abstract: The combination of immunotherapy with other forms of treatment is an emerging strategy for boosting antitumor responses. By combining multiple modes of action, these combinatorial therapies can improve clinical outcomes through unique synergisms. Here, a microrobot‐based strategy that integrates tumor tissue disruption with biological stimulation is shown for cancer immunotherapy. The microrobot is fabricated by loading bacterial outer membrane vesicles onto a self‐propelling micromotor, which can react with water to generate a propulsion force. When administered intratumorally to a solid tumor, the disruption of the local tumor tissue coupled with the delivery of an immunostimulatory payload leads to complete tumor regression. Additionally, treatment of the primary tumor results in the simultaneous education of the host immune system, enabling it to control the growth of distant tumors. Overall, this work introduces a distinct application of microrobots in cancer immunotherapy and offers an attractive strategy for amplifying cancer treatment efficacy when combined with conventional therapies. Abstract : Micromotors coated with bacterial membrane are utilized for combinatorial cancer therapy. Upon intratumoral administration, the micromotors induce irreversible physical damage to the tumor tissue, while the immunostimulatory membrane recruits host immune cells to process tumor antigens in situ. Treatment of solid tumors using this platform results in robust antitumor immunity that can also control the growth of distant secondary tumors.